Assessing the current situation of constructed wetland-microbial fuel cells as an alternative power generation and wastewater treatment in developing countries - Jacobs, Damien Georges; Kachienga, Leonard Owino; Rikhotso, Mpumelelo Casper; Abia, Akebe Luther King; Traoré, Afsatou Ndama; Potgieter, Natasha (Frontiers in Energy Research, 2024)
Developing countries facing population growth and increased energy demand present simultaneous challenges regarding wastewater treatment and electricity supply. Constructed wetland-microbial fuel cells (CW-MFCs) offer a dual solution to the challenges of insufficient electricity and wastewater treatment by integrating indigenous plant species. CW-MFCs provide sustainable power generation and wastewater treatment. This approach can enhance sustainability and foster a circular economy by utilising plant-derived byproducts as an added product. Current research indicates various novel designs for effective wastewater treatment and potential power generation. Future studies focusing on rural settings and upscaling operations can apply advanced techniques like mass spectrophotometry and metagenomics to refine the technology for grid use. Developing CW-MFC technology will catapult the idea of developing a robust strategy for addressing power supply and sanitation issues in developing regions. This will also aid in continuous research into system optimisation and microbial communities, aiding long-term viability.